Euro area house price fluctuations and unconventional monetary policy surprises - Oliver Hülsewig; Horst Rottmann (Ostbayerische Technische Hochschule Amberg-Weiden (OTH), 2021)
This paper examines the reaction of house prices in a panel of euro area countries to monetary policy surprises over the period 2010-2019. Using Jordà's (2005) local projection method, we find that house prices rise in response to expansionary monetary policy shocks that can be related to unconventional monetary policy measures. Thus, monetary policy should take into account the risk of house price fluctuations when implementing new large scale policy interventions.
Keywords: E52; E58; E32; G21; 330; House price fluctuations; unconventional monetary policy; local projection method